A shining light [large type] - Miller, Judith, 1944- (Miller, Judith, 1944- Home to Amana, 2014)
West Amana, Iowa, 1890. After Andrea Wilson receives the devastating news that her husband has been lost at sea, she returns home to Iowa with her young son, Lukas. But what she finds there causes more heartache: The family farm has burned and her father has died, leaving Andrea with nothing. Andrea must rely on the kindness of the people from the nearby Amana village who invite her to stay with them for a time. She discovers much generosity and contentment among the Amanans -- especially from the tinsmith, Dirk Knefler, who takes her son under his wing. But is the simple, cloistered life in Amana what Andrea wants for Lukas's future? Is she willing to give up the comforts and freedom of the outside world? And when yet another round of shocking news comes her way, will Andrea ever be able to find the serenity and hope that have eluded her for so long?